At least two nuclear proteins bind specifically to the Rous sarcoma virus long terminal repeat enhancer. - Sealey, L (1987)
We used the sensitive gel electrophoresis DNA-binding assay and DNase I footprinting to detect at least two protein factors (EFI and EFII) that bound specifically to the Rous sarcoma virus (RSV) enhancer in vitro. These factors were differentially extracted from quail cell nuclei, recognized different nucleotide sequences in the U3 region of the RSV long terminal repeat, and appeared to bind preferentially to opposite DNA strands as monitored by the DNase I protection assay. The EFI- and EFII-protected regions within U3 corresponded closely to sequences previously demonstrated by deletion mutagenesis to be required for enhancer activity, strongly suggesting a functional significance for these proteins. Only weak homologies between other enhancer consensus sequence motifs and the EFI and EFII recognition sites were observed, and other viral enhancers from simian virus 40 and Moloney murine sarcoma virus did not compete effectively with the RSV enhancer for binding either factor.